2022
DOI: 10.21203/rs.3.rs-2285240/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The therapeutic monoclonal antibody bamlanivimab does not enhance SARS‑CoV-2 infection by FcR-mediated mechanisms

Abstract: Background Antibodies targeting envelope glycoproteins have been shown in some instances to enhance infection by subverting Fc receptor and complement function, or by directly inducing fusion with cellular membranes. The potential for antibody dependent enhancement (ADE) of infection raises concern that passive immunization with a therapeutic anti-viral antibody could increase risk of disease. As part of the nonclinical package characterizing the risk profile of the SARS-CoV-2 neutralizing monoclonal antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, data showing that ADE is important in vivo is lacking and one recent study showed that although an infection-enhancing effect of human neutralizing antibodies was observed in vitro, the same neutralizing antibodies exhibited a protective effect in vivo, when infused into mice or macaques (Li et al, 2021). Another recent analysis using both in vitro and in vivo experiments involving BAM also found no support for it generating ADE of SARS-CoV-2 infection (Cross et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, data showing that ADE is important in vivo is lacking and one recent study showed that although an infection-enhancing effect of human neutralizing antibodies was observed in vitro, the same neutralizing antibodies exhibited a protective effect in vivo, when infused into mice or macaques (Li et al, 2021). Another recent analysis using both in vitro and in vivo experiments involving BAM also found no support for it generating ADE of SARS-CoV-2 infection (Cross et al, 2022).…”
Section: Discussionmentioning
confidence: 99%